Variability of ankle kinematics in professional cyclists: consequence on saddle height adjustment - Millour, G.; Duc, S.; Ouvrard, T.; Segui, D.; Puel, F.; Bertucci, W. (Journal of Science and Cycling, 2020)
Bike-fitting methods based on the knee kinematics have been developed to determine the optimal saddle height. Among them, the Ferrer-Roca method advises a knee angle between 30 and 40° in the sagittal plane when the crank arm is aligned with the seat tube while pedalling. However, the foot orientation varies between individuals and can influence the knee angle throughout the pedalling cycle. The objective of this study was to measure the inter-individual variability in joint kinematics of professional cyclists and to evaluate the influence of the ankle angle modification on the knee angle during pedalling. Seventeen professional cyclists performed a 3-min pedalling test at 150 W and 80 rpm on their personal road bike mounted on an Elite Turno® ergometer (Elite, Fontaniva, Italia). The knee and ankle angles were measured using 2D kinematic analysis. The average knee angle (38°) was in the optimal range of 30-40°, but great variability was observed between individuals (coefficient of variation of 11.8% and 9.4% for knee and ankle angles, respectively). Moreover, five of them had a knee angle greater than 40°. In addition, their ankle angle was 15% lower than that of cyclists who had a knee angle between 30 and 40° (50 ± 4° vs. 58 ± 4°, p < 0.05). The results suggest that the knee angle observed when professional cyclists use their preferred saddle height varies among individuals and is related to the foot orientation while pedalling. The maximum knee extension angle is lower for the cyclists who accentuate the dorsiflexion but greater for those who pedalled with a plantarflexion. This implies that the saddle height adjustment method based on the knee kinematics while pedalling should consider both the knee and ankle angles.